PENGARUH KEMANDIRIAN BELAJAR, MINAT BELAJAR, LINGKUNGAN KELUARGA, TEMAN SEBAYA DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA KELAS X XI PADA MATA PELAJARAN EKONOMI DI SMA N 2 HILIRAN GUMANTI - Afdilla; Jolianis; Putri, Yosi Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the influence of learning independence, interest in learning, family environment, peers, and school environment partially and simultaneously on students' learning motivation in economics subjects at SMA Negeri 2 Hiliran Gumanti district. Solo. This type of research is quantitative with an associative method. This research was carried out in July 2025. The sample in this research was all students in class XI and class XII who took economics subjects totaling 74 people. The sampling technique is Total Sampling. The analysis technique uses descriptive analysis and inductive analysis using multiple linear regression with the help of the Spss and Eviews programs. The research results show: 1) Learning independence has a positive and significant effect on learning motivation, with a coefficient value of 0.169. This value is significant because tcount 2.087 > ttable 1.6672, thus H0 is rejected and Ha is accepted. Thus, if learning independence increases by one unit, then students' motivation to learn increases by 0.169 for each unit. 2) Interest in learning has a positive and significant effect on learning motivation, with a coefficient value of 0.145. This value is significant because tcount 2.540 > ttable 1.6672, thus H0 is rejected and Ha is accepted. This means that if interest in learning increases by one unit, then students' learning motivation increases by 0.145 for each unit. 3) The family environment has a positive and significant effect on learning motivation, with a coefficient value of 0.165. This value is significant because tcount 3.006 > ttable 1.6672, meaning that H0 is rejected and Ha is accepted. Thus, if the family environment increases by one unit, then students' motivation to learn increases by 0.165 for each unit. 4) Peers have a positive and significant influence on learning motivation, with an coefficient value of 0.219. This value is significant because tcount 2.630 > ttable 1.6672, meaning that H0 is rejected and Ha is accepted. Thus, if learning independence increases by one unit, then student learning motivation increases by 0.219 for each unit. 5) The school environment has a positive and significant effect on learning motivation, with an coefficient value of 0.139. This value is significant because tcount 2.128> ttable 1.6672, meaning that H0 is rejected and Ha is accepted. Thus, if learning independence increases by one unit, then student learning motivation increases by 0.139 for each unit. 6) learning independence, interest in learning, family environment, peers, and school environment together have a significant influence on learning motivation. Where the fcount value is 16.093 > ftable 2.505. This shows that Ha is accepted and H0 is rejected. The coefficient of determination value of 0.542 means that the variables of learning independence, interest in learning, family environment, peers and school environment have a significant effect on learning motivation by 54.2%. It is recommended that to increase learning motivation, you must increase learning independence, interest in learning, family environment, peers and school environment in class XI and XII students in Economics subjects at SMA Negeri 2 Hiliran Gumanti.